2022
DOI: 10.1039/d1dt03571a
|View full text |Cite
|
Sign up to set email alerts
|

On the magnetic structure and magnetic behaviour of the most distorted member of the series of RNiO3 perovskites (R = Lu)

Abstract: The crystal structure of LuNiO3 perovskite has been examined below RT and across TN = 125 K by neutron powder diffraction. In this temperature region (2-298 K), well below the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In the literature, it is reported that the YNiO 3 nickelate undergoes the structural transition P 2 1 / n → Pbnm at 14 GPa, followed by a drop in the optical bandgap and a step-jump of the lattice parameter c , which is also featured by compressibility variations. Indeed, these anomalies along the lattice parameters are a common signature of the charge rearrangement to stabilize the metallic state in small R cation nickelates. ,, Then, the anomaly at 10.8 GPa in Figure c is a strong evidence for the structural phase transition P 2 1 / n → Pbnm . Besides, by similarity, we may hypothesize that this transition is accompanied by the IMT as for YNiO 3 and TlNiO 3 belonging to the same nickelate group with small R cation size; however, the final confirmation of this assumption needs additional measurements by means of infrared spectroscopy and/or resistivity.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…In the literature, it is reported that the YNiO 3 nickelate undergoes the structural transition P 2 1 / n → Pbnm at 14 GPa, followed by a drop in the optical bandgap and a step-jump of the lattice parameter c , which is also featured by compressibility variations. Indeed, these anomalies along the lattice parameters are a common signature of the charge rearrangement to stabilize the metallic state in small R cation nickelates. ,, Then, the anomaly at 10.8 GPa in Figure c is a strong evidence for the structural phase transition P 2 1 / n → Pbnm . Besides, by similarity, we may hypothesize that this transition is accompanied by the IMT as for YNiO 3 and TlNiO 3 belonging to the same nickelate group with small R cation size; however, the final confirmation of this assumption needs additional measurements by means of infrared spectroscopy and/or resistivity.…”
Section: Resultsmentioning
confidence: 89%
“…For instance, the nickelates comprising large R cations and low electronegativity result in large bond-angle, such as the rhombohedral LaNiO 3 [ r La = 1.36 Å; Θ = 165.2(1)°], exhibiting a metallic behavior at room temperature. For small and medium R cation size nickelates, their low-temperature insulator state is associated with the monoclinic P 2 1 / n crystal structure, where a charge disproportionation along Ni sites is observed, while its metallic state is featured by an orthorhombic unit cell with the Pbnm space group in which the Ni charges are homogeneously distributed. Indeed, the small R cation nickelates (also referred to as highly distorted) with low bond-angle Θ, such as LuNiO 3 [ r Lu = 0.977 Å; Θ = 144.4(1)°], become metallic only at high temperature when Θ increases (for LuNiO 3 , the IMT takes place at 600 K). , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations